ABOUT THE SECRETS OF FRENCH ARTICLES (Scientific journal of the Fergana State University, 2024)
This article analyzes the different approaches to the use of articles in French and how these articles are expressed in translations. In French, the article plays a big role not only in expressing meaning, but also in highlighting meaning and defining the boundaries of meaning. An article is a word that stands before a noun and serves to define it, and can also be an indicator of gender and number. Articles in French perform an important grammatical function: they indicate the gender and number of nouns, and also serve to express the categories of definiteness and uncertainty. In this language, the article is an auxiliary word that modifies a noun. The article analyzes how these articles are expressed and changed in translations. In this article, the author examines the use of articles, as well as some of their features.To translate French texts into a particular language, it is necessary to determine the meaning of the articles used in the text. In the article, the author analyzed in detail how articles are reflected when translated through sentences.